REVITALISASI KEGIATAN KEAGAMAAN DALAM PROGRAM KKS-T: MEMBANGUN KARAKTER DAN PEMBERDAYAAN BERKELANJUTAN DI DESA HUYULA, GORONTALO - Mooduto, Dzulkifli M.; Ibrahim, Zulkarnain; Paputungan, Mohamad Haikal; Oalo, Mutia; Muasomah; Khasna, Syarifa (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
The revitalization of religious activities within communities is an essential effort in character building and strengthening social values. The Thematic Social Work Program (KKS-T) in Huyula Village, Gorontalo, serves as a strategic platform to realize this goal through community empowerment. This study aims to describe the implementation of religious activity revitalization in the KKS-T program using the Asset-Based Community Development (ABCD) approach. A qualitative descriptive method with a participatory approach was employed, in which students of KKS-T from IAIN Sultan Amai Gorontalo designed and carried out the “Semarak Ramadan” program as a medium of empowerment based on local assets, positioning the community as the main actor. A series of activities—including planning, opening ceremony, children's Islamic festival, Ramadan bazaar, Huyula Awards, and closing event—created productive spaces for social and spiritual interaction. The findings show that through collaboration among students, village authorities, community leaders, and local residents, religious activities can become effective instruments in fostering spiritual awareness, social solidarity, and supporting sustainable community empowerment at the village level.